Meditation in Philosophical Practice as “Live Metaphysics” (Meditation Practices of the Stoic School) - Fabjański, Marcin Piotr (Folia Philosophica, 2021)
This article argues that if contemporary philosophical counseling wishes to perpetuate the spirit of ancient philosophy, it must also incorporate metaphysics. This kind of incorporation means, among other things, regarding as essential the implementation of the meditation practices of certain historical schools of philosophy. Meditation was an inherent feature not only of Eastern schools of thought, but also within Western philosophy (as the author demonstrates through the example of Marcus Aurelius’ Meditations). These practices lead to a psychophysical state, known as ataraxia, which causes the perception of reality to undergo a radical change, including occasional “altered states of consciousness,” as they are known by psychology. The author calls such practices “live metaphysics.” He also maintains that, without the inclusion of such metaphysical practices, philosophical counselling and coaching lose their eudemonic character and become a means of hedonistic gratification in the service of the liberated ego of the contemporary man.